Extraction or nonextraction in orthodontic cases: A review - Sagar Mapare; Ram Mundada; Arjun Karra; Shivam Agrawal; Sushil Bhagwan Mahajan; Ashutosh Tadawalkar (Wolters Kluwer Medknow Publications, 2021)
Orthodontic treatment helps bring teeth in alignment. There is always debate whether tooth should be extracted or not for treating crowding. The present article highlights various advantages and disadvantages of extraction.